Optimum phase ratio in the triple jump - Yu, B.; Hay, J. G. (Journal of Biomechanics, 1996)
The purpose of this study was to develop and validate a method to determine the optimum phase ratio that yields the longest actual distance for a given triple jumper. Two hypotheses were tested: (a) for any given triple jumper, the greater the gain in the vertical velocity the greater the loss in the horizontal velocity; and (b) there is no single optimum phase ratio for all triple jumpers. Kinematic data were collected for four elite male triple jumpers. It was found that the loss in the horizontal velocity during a support phase has a significant positive linear correlation with the gain in the vertical velocity during the same support phase. The slope of the regression line was referred to as the horizontal-to-vertical velocity conversion factor. Based on this relationship, an optimization model for the longest actual distance was developed to determine the optimum phase ratio for each of the four subjects. The optimization results showed that there was an optimum phase ratio for the longest actual distance for each triple jumper. The results of a validity test showed that the model predicted the actual distance with a degree of fair accuracy. The results of sensitivity analysis showed that the optimum phase ratio for a given athlete was a function of the horizontal-to-vertical velocity conversion factor and the horizontal velocity at the touchdown of the hop. These results support the two hypotheses of this study.